Resilience: decisive factor for growth and improvement of organizations - Serna Silva, Giovanna (2018)
The term of globalization according to some scholars appears and begins to be used in 1771 and the consequent diffusion makes it arrive at different scopes and today more frequently and circumscribed to the companies, where they have the necessity of first to unlearn and then to learn; That is, to unlearn their traditional ways of making and making decisions, with the sole purpose of remaining in this market that is highly competitive. However, as companies continue to make changes, there is a possibility that work problems will intensify and thus create an inadequate organizational climate. In this sense, the present article raises the importance of the resilience in the companies, since its application contributes to improve the capacity to adapt successfully and to teach the proper way to the progress and not only to its survival.